Enhancing phytoremediation of bauxite mine subsoil by Jatropha curcas L. using sewage sludge and poultry sludge - Lim, Mingyuan; Samsuri, Abd. Wahid; Abd Shukor, Mohd. Yunus; Phang, Lai-Yee (Springer Nature, 2024)
Phytoremediation is a sustainable technology for cleaning up heavy metal contamination at mining sites. However, degraded soils at these sites create a harsh environment for plants to survive and properly yield biomass. In this study, sewage sludge and poultry sludge were applied as soil amendments in bauxite mine subsoil to determine their impact on the growth and heavy metal uptake of Jatropha curcas L. Both sewage sludge and poultry sludge were applied at 25% and 50%. J. curcas was grown in the amended soils for 120 days under greenhouse conditions. Changes in soil physico-chemical properties, plant growth and heavy metal uptake of J. curcas were determined after that. An increase in EC, CEC, total C, total N, total available P and total extractable K was detected in the amended soils. These improvements enhanced the growth of J. curcas, particularly in the development of above-ground plant biomass. Increased plant biomass subsequently led to higher bioaccumulation and translocation efciency of Al, Fe, Pb and Zn. As a result, higher heavy metal removal of up to 98.03% was detected in the amended treatments. The fndings indicated that the application of sewage sludge and poultry sludge improves soil conditions for plant development.